2017
DOI: 10.1016/j.socscimed.2017.01.053
|View full text |Cite|
|
Sign up to set email alerts
|

“They treated me like crap and I know it was because I was Native”: The healthcare experiences of Aboriginal peoples living in Vancouver's inner city

Abstract: There is growing evidence that Aboriginal peoples often experience healthcare inequalities due to racism. However, research exploring the healthcare experiences of Aboriginal peoples who use illicit substances is limited, and research rarely accounts for how multiple accounts of stigma intersect and contribute to the experiences of marginalized populations. Our research aimed to explore the healthcare experiences of Aboriginal peoples who use illicit drugs and or illicit alcohol (APWUID/A) living in Vancouver’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
175
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 59 publications
4
175
1
1
Order By: Relevance
“…These experiences Research have a significant impact on health. [29][30][31][32] These routine experiences of discomfort and shame when interacting with the health care system can contribute to higher rates of cost-related nonadherence, for example, because Indigenous patients may avoid consultations with physicians and pharmacists or may cut visits short without obtaining the necessary information. 33 The prevalence of cost-related nonadherence in our study, 8.2%, is slightly lower than comparable past estimates: we previously found that 9.6% of those with a prescription in 2007 experienced cost-related nonadherence.…”
Section: Discussionmentioning
confidence: 99%
“…These experiences Research have a significant impact on health. [29][30][31][32] These routine experiences of discomfort and shame when interacting with the health care system can contribute to higher rates of cost-related nonadherence, for example, because Indigenous patients may avoid consultations with physicians and pharmacists or may cut visits short without obtaining the necessary information. 33 The prevalence of cost-related nonadherence in our study, 8.2%, is slightly lower than comparable past estimates: we previously found that 9.6% of those with a prescription in 2007 experienced cost-related nonadherence.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Therefore, disproportionate rates of mental illness and suicidality must be understood in context, not as intrinsic predispositions of Indigenous people but instead as reflecting persistent inequities. 2,[7][8][9][10] This is evident for many Indigenous people living in inner cities where the effects of poverty, racism, and other layers of discrimination and marginalization on mental health are impossible to overlook. 8,9,11,12 In general, mental health services in urban settings have not been adapted to serve the needs of Indigenous patients, and this is reflected in the comparatively low rates of voluntary utilization, 13,14 and much higher rates of acute admissions to hospital for suicidality and other mental health crises.…”
mentioning
confidence: 99%
“…2,[7][8][9][10] This is evident for many Indigenous people living in inner cities where the effects of poverty, racism, and other layers of discrimination and marginalization on mental health are impossible to overlook. 8,9,11,12 In general, mental health services in urban settings have not been adapted to serve the needs of Indigenous patients, and this is reflected in the comparatively low rates of voluntary utilization, 13,14 and much higher rates of acute admissions to hospital for suicidality and other mental health crises. 15 Qualitative studies point to numerous reasons why Indigenous people express reluctance to engage with mainstream health care services: including racism, "being treated as a second-class citizen," and lack of Indigenous staff and cultural practices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used in this study have been described in detail elsewhere (Goodman et al, 2017). Indigenous knowledge is premised upon oral traditions so the community research team selected talking circles as a culturally appropriate conversational research method (Kovach, 2010).…”
Section: Methodsmentioning
confidence: 99%